Fighting childhood pneumonia in Uganda - Calkins, Tim ([London] : SAGE, 2016)
It is January 2014, and the case protagonist, David Milestone (senior advisor at the Center for Accelerating Innovation and Impact at the U.S. Agency for International Development's Global Health Bureau), is preparing for a meeting of global stakeholders and pharmaceutical manufacturers who are interested in reducing mortality caused by childhood pneumonia and are prepared to donate $10 million to support this effort. Milestone's goal is to propose a strategy to address childhood pneumonia in Uganda, toward which the $10 million donation would go. This text examines these efforts.
Originally Published in: Calkins, T., Palamountain, K., Chatterjee, A., Frantz, R., Hart, E., Mathewson, S., & Perez-Hobrecker, G. (2015). Fighting Childhood Pneumonia in Uganda. 5-413-755. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Pneumonia in children; Health services administration -- Uganda -- Case studies; Public health -- Case studies; Social entrepreneurship -- Case studies